A rare CYP21A2 mutation in a congenital adrenal hyperplasia kindred displaying genotype–phenotype nonconcordance. Issue 1 (20th August 2015) - Khattab, Ahmed; Yuen, Tony; Al‐Malki, Sultan; Yau, Mabel; Kazmi, Diya; Sun, Li; Harbison, Madeleine; Haider, Shozeb; Zaidi, Mone; New, Maria I.
Abstract : Congenital adrenal hyperplasia (CAH) owing to 21‐hydroxylase deficiency is caused by the autosomal recessive in‐heritance of mutations in the gene CYP21A2 . CYP21A2 mutations lead to variable impairment of the 21‐hydroxylase enzyme, which, in turn, is associated with three clinical phenotypes, namely, salt wasting, simple virilizing, and nonclassical CAH. However, it is known that a given mutation can associate with different clinical phenotypes, resulting in a high rate of genotype–phenotype nonconcordance. We aimed to study the genotype–phenotype nonconcordance in a family with three siblings affected with nonclassical CAH. All had hormonal evidence of nonclassical CAH, but this phenotype could not be explained by the genotype obtained from commercial CYP21A2 genetic testing, which revealed heterozygosity for the maternal 30 kb deletion mutation. We performed Sanger sequencing of the entire CYP21A2 gene in this family to search for a rare mutation that was not covered by commercial testing and found in the three siblings a second, rare c.1097G>A (p.R366H) mutation in exon 8. Computational modeling confirmed that this was a mild mutation consistent with nonclassical CAH. We recommend that sequencing of entire genes for rare mutations should be carried out when genotype–phenotype nonconcordance is observed in patients with autosomal recessive monogenic disorders, including CAH.